Avaliação técnica e econômica do uso do soro de queijo de coalho na alimentação de suínos - SILVA, Edmilson Gomes da (2008)
The use of curd cheese whey in swine alimentation was evaluated through an metabolism experiment using eighteen barrows with an average live weight of 37,1±1,7 kg. Nine animals were allotted in an experimental randomized block design with three treatments and three repetitions in each one of the assays repeated in the time.The treatments had consisted a reference ration (RR), RR with water in the ratio of 1:1,5 and one treatment with whey substituting 18% RR in dry matter basis. The animals were lodged in metabolic crates, adapted during seven days and submitted to five collection days. The method of total excreta collection was adopted with use of ferrous oxide as external marker. The collected feces were weighed, an aliquot of 20% weretaken and after that congealed. The urine collected were weighed, an aliquot of 5% were taken and after that stored in refrigerator. Samples of excreta, whey and RR were analyzed following methodology of the AOAC (2002). The curd cheese whey evaluated presented 5,16% of dry matter, 0,83% of crude protein, 0,8% ether extract and 190,5 kcal/kg of Metabolizable Energy. The curd cheese whey is an alternative food prone for swine feeding. Paste feeding didn´t promote changes in digestibility and retention of diet nutrients and energy.